Efektivitas Media Papan Pintar Terhadap Kemandirian Belajar Kelas IV SD Negeri Mangkubumen Wetan Surakarta - Rizky; Ema Butsi Prihastari; Mukhlis Mustofa (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This study aims to determine the effectiveness of using smart board media on the learning independence of fourth-grade students at SDN Mangkubumen Wetan, Surakarta. The background of the study is based on the low level of student learning independence, as indicated by a lack of self-confidence, high dependence on teachers, and minimal active participation in the learning process. The study employed a quantitative approach with a one-group pretest-posttest design. The research subjects consisted of 28 students selected using a saturated sampling technique. Data were collected through a learning independence questionnaire, observation, and documentation. The research instruments were tested for validity and reliability. Data analysis included normality testing, paired sample t-test, and N-Gain test. The results showed that the average pretest score was 70.62 (71%), and the posttest score was 86.38 (86%). The paired sample t-test showed a significance value of 0.000 (< 0.05) and a t-value of 11.941 > t-table value of 2.052, indicating a significant difference between the pretest and posttest scores. Furthermore, the N-Gain test results showed an increase of 62.49, which is categorized as moderately effective in improving the learning independence of fourth-grade students in mathematics at SDN Mangkubumen Wetan Surakarta.